Zn1−xMg xO thin films as a sustainable layer for CZTSSe solar cells - Prabeesh Punathil; Stephen Campbell; Giray Kartopu; Pietro Maiello; Oliver S Hutter; Vincent Barrioz; Neil S Beattie; Guillaume Zoppi (JPhys Energy)
Traditionally, CdS serves as the buffer layer in Cu _2 ZnSn(S,Se) _4 (CZTSSe) solar cells, but poses issues such as toxicity, optical losses, and a suboptimal conduction band offset (CBO). This study explores the use of Zn _1− _x Mg _x O (ZMO, 0 ⩽ x ⩽ 1) thin films as a potential buffer layer for CZTSSe solar cells, deposited by magnetron sputtering. ZMO thin films were characterized for composition, energy band gap, structural, and surface properties. The band gap of ZMO films varied from 3.21 eV to 4.88 eV with increasing Mg content. Structural analysis indicated that higher Mg content led to lattice strain and phase segregation, while surface morphology showed an initial increase in grain size with increasing Mg concentration, which then decreased at higher Mg concentrations. The performance of photovoltaic devices was found to be dependent on the Mg content in the film, and the highest efficiency of 3.33% was obtained for x = 0.16. ZMO-based devices exhibited a better open-circuit voltage due to a more favourable CBO compared to CdS-based devices. However, despite their improved photo response in the blue region attributed to ZMO’s wider band gap, these devices showed lower short-circuit current and overall efficiency compared to CdS counterparts. To understand the lower performance of ZMO-based devices compared to standard CdS devices, capacitance–voltage and photoluminescence measurements, as well as solar cell capacitance simulator device simulations were conducted, revealing insights into the performance limitations of ZMO as a buffer layer.